ANALYSIS OF FACETOPLASTY APPLICATION FOR ISOLATED FACET SYNDROME IN PATIENTS WITH DEGENERATIVE DISEASE OF ZYGAPOPHYSIAL JOINTS OF THE LUMBAR SPINE - A. A. Kalinin; A. K. Okoneshnikova; A. A. Irintseev (Инновационная медицина Кубани)
Background. Degenerative diseases of zygapophysial joints of the lumbar spine are the main reason of a resistant facet syndrome in 70–85% of the population older 40 years. This research was aimed to carry out an analysis of results after facetoplasty used for treating patients with degenerative diseases of zygapophysial joints of the lumbar spine.Material and methods. The research included 128 patients at the age of 41 (35.5; 46) years with degenerative diseases of zygapophysial joints of the lumbar spine and clinical manifestations in the form of an isolated facet syndrome. They have had puncture of zygapophysial joints with intra articulate introduction of joint fluid prosthesis (facetoplasty) within the period from 2015 to 2017. We used a visual analogue scale of pain and the Osvestri questionnaire for patients with problems in the back to assess clinical efficiency. Dynamic assessment was made in average in 24 months after the operation.Results. As a result it is found out that the facetoplasty is an effective mini-invasive method for facet syndrome treatment, caused by degenerative diseases of zygapophysial joints of the lumbar spine.Conclusion. Usage of facetoplasty in patients with isolated FS caused by degenerative disease of zygapophysial joints of the lumbar spine allows to observe sufficient clinical outcomes within immediate and long-term postoperative periods.